DISASTER RISK ANALYSIS OF FOREST AND LAND FIRES IN SERANG REGENCY - Raharjo, Akhmadi Puguh (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2018)
Forest and land fires (Karhutla) is one of the disasters that frequently hit Indonesia every year. Assessment for Karhutla's hazard, vulnerability and risk is an important early instrument for determining future disaster mitigation measures. The purpose of this study was to perform disaster risk assessment for Karhutla based on forest and land fires hazard and social vulnerability in the Regency of Serang. This particular hazard, vulnerability and risk analysis was based on the guidance outlined in the Head of BNPB Regulation No. 2 of 2012. The analysis results show that 46.87% of the total settlement area in the Regency of Serang falls into the low risk class of Karhutla. Meanwhile, medium and high risk class of Karhutla accounted for approximately 37.78% and 0.90% of the total settlement area in the Regency of Serang, respectively. Future detailing is needed to obtain more detailed results in the future.